A proposal for enhanced microstructural development of Poly(ethylene 2, 5-furandicarboxylate), PEF, upon stretching: On strain-induced crystallization and amorphous phase stability improvement. (19th April 2022) - Forestier, Emilie; Combeaud, Christelle; Guigo, Nathanael; Sbirrazzuoli, Nicolas
Abstract: Poly(ethylene 2, 5-furandicarboxylate), PEF, has been described regarding its ability at developing strain-induced crystallization (SIC). The influence of several stretching settings on its microstructural development has been investigated. Based on the time/temperature superposition principle, the stretching settings have been chosen to draw the material in its rubbery-like state. Two equivalent strain rates, defined at the reference temperature of 100 °C, have been selected. For each equivalent strain rate, two strain rate/temperature couples ("slow" and "rapid") are selected. It appears that the strain rates ("slow" or "rapid") have an influence on the induced microstructure in terms of crystal perfection, amorphous phase rigidity and thermal stability. Depending on the strain rate, the presence (for "rapid" tests) or the absence (for "slow" tests) of self-heating upon stretching is reported. Indeed, it could be the key point to determine the final definition of the crystal obtained. Additionally, the amorphous domain mobility is impacted: the stability of the amorphous domain with temperature has been increased with the use of "rapid" conditions. SIC occurs for all the stretching settings applied but the use of couples with rapid strain rates/high temperatures could be more efficient to improve the microstructure definition and stability: these results are of prime interest regarding industrial applications such as ISBM (Injection Stretch Blow Moulding) or thermoforming. Graphical abstract: Image 1 Highlights: PEF and PET mechanical behaviour both obey to time/temperature equivalence principle. For all the stretching settings applied, a strain-induced crystal has been developed in PEF and PET. Enhanced induced microstructures are obtained by stretching PEF and PET with higher strain rates, promoting self-heating.